La reforma constitucional en el Perú: implicaciones y retos - García Toma, Víctor Óscar Shiyin (2013)
In this article, the author points the possibitity of a Constitutional Reform as a way to change the Constilution. This measure will only he possible when the Constituent Power itself expressly authorizes the orcUnary legislature to become into a Creative ofthe constitutional order. Finally, the author indícales that the unconstitutionality of the Constitutional Reform will he given to the extent that the national authority, in this case the Constitutional Court, viólales the formal limits for the reform, or the material limits, which are aimed at preserving the constitutional essence the content ofthe Constilution.